Desirable Difficulties in Spatial Learning: Testing Enhances Subsequent Learning of Spatial Information - Bufe, Jonathan; Aslan, Alp (Frontiers in Psychology, 2018)
Previous work has shown that testing can enhance learning and retention of subsequently studied new information. The present study investigated this forward testing effect in spatial memory. In two experiments, participants studied four successively presented 3 × 3 arrays, each composed of the same nine objects. They were asked to memorize the locations of the objects which differed across the four arrays. Following presentation of Arrays 1–3, memory for the object locations of the respective array was tested (testing condition), or the array was re-presented for additional study (restudy condition). Thereafter, Array 4 was presented and tested in both the testing and the restudy condition. In Experiment 1, testing was self-paced, whereas in Experiment 2, testing time was controlled by the experimenter. Consistent across the two experiments, testing was found to enhance location memory for Array 4, relative to restudying. Furthermore, testing also reduced the number of confusion errors (i.e., the tendency to misplace objects to locations on which they had appeared previously) made during recall of Array 4, suggesting that testing reduced the interference potential of prior information. The results indicate that testing can enhance subsequent learning of spatial information by reducing the build-up of proactive interference from previously studied information.